1996
DOI: 10.1111/j.1476-5381.1996.tb15389.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lacidipine on fatty and proliferative lesions induced in hypercholesterolaemic rabbits

Abstract: 1 The in vivo antiatherogenic activity of the calcium antagonist, lacidipine, was investigated in two different types of atherosclerotic lesions (proliferative and fatty lesions) induced in rabbits. 2 The proliferative lesion was obtained by positioning a hollow silastic collar around one carotid artery, while aortic fatty lesions were induced by cholesterol feeding. Cholesterol (1%) and lacidipine (1, 3, and 10 mg kg-') were given daily mixed with standard diet for 8 weeks to White New Zealand rabbits. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…Second, the inverse relationship between CA distensibility and 24-h BP did not usually extend to diastolic values. This adds mechanistic evidence to the conclusion of several studies that SBP may be a better predictor of cardiovascular disease than DBP [29][30][31][32][33], because arterial stiffening increases the mechanical effect of intravascular pressure on the vessel wall, thereby favouring atherosclerosis [31,34]. Third, CA distensibility showed an inverse relationship with SBP variability.…”
Section: Discussionmentioning
confidence: 75%
“…Second, the inverse relationship between CA distensibility and 24-h BP did not usually extend to diastolic values. This adds mechanistic evidence to the conclusion of several studies that SBP may be a better predictor of cardiovascular disease than DBP [29][30][31][32][33], because arterial stiffening increases the mechanical effect of intravascular pressure on the vessel wall, thereby favouring atherosclerosis [31,34]. Third, CA distensibility showed an inverse relationship with SBP variability.…”
Section: Discussionmentioning
confidence: 75%
“…The antiatherosclerotic action of lacidipine was reproduced in many in vivo and in vitro studies. It includes an improvement of endothelial dysfunction and permeability, a decrease in smooth muscle cell proliferation and oxidation of low-density lipoproteins, and a reduction in adhesion molecule (ICAM-1, VCAM-1, and E-selectin) expression in tumor necrosis factor-a-stimulated endothelial cells [12][13][14][15]. Furthermore, its antioxidant effect is most strongly expressed as compared to other calcium channel blockers [20].…”
Section: Discussionmentioning
confidence: 92%
“…Its antiatherosclerotic effects include inhibition of fatty streak formation, reduction of cellular adhesion molecule expression, antioxidant effects, and improving endothelial dysfunction in hypertensive patients [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…1 Among calcium antagonists, highly lipophilic, antioxidant, long-acting dihydropyridines such as lacidipine 2,3 were found to be particularly effective in experimental models of atherosclerosis. 4,5 B-mode ultrasound examination of the carotid arteries with measurement of intima-media thickness (IMT) has been used as a measure of asymptomatic atherosclerosis progression. 6 Three randomized trials of antihypertensive therapy showed smaller progression or greater regression of carotid lesions in patients treated with a calcium antagonist rather than a diuretic, [7][8][9] but the changes were small and the trials had limited power to detect these differences.…”
mentioning
confidence: 99%